INTERNATIONAL LEGAL AND DOMESTIC LEASING REGULATION AT THE CURRENT STAGE OF GOVERNMENT ADMINISTRATION IMPLEMENTATION IN THE CONDITIONS OF SCIENTIFIC AND TECHNOLOGICAL DEVELOPMENT - Vakhitov , Damir; Samovich , Yulia; Nurtdinov , Ilgiz; Sharifullin , Ramil; Gumerov , Lenar (Revista Inclusiones, 2020)
Leasing is one of the most important and dynamically developing forms of investing free cash in production and a tool to stimulate the renewal of fixed assets of economic entities and progress in the scientific and technological field. With a variety of advantages, leasing activities are pervasive as a form of direct investment. However, progressive development of this type of financial transactions is possible with a competent combination of public administration with the methods of fiscal and customs policy, which inevitably brings up a problem of combining foreign economic policy and foreign policy activities of different countries. The article is devoted to the analysis of the legal regulation of leasing relations in accordance with the norms of international Convention and Russian legislation, as well as consideration of paces and features of the leasing development in the Russian Federation during 2017-2018 and identification of problems of the domestic leasing market in the context of scientific and technological progress.